2019
DOI: 10.1021/acs.chemmater.8b04642
|View full text |Cite
|
Sign up to set email alerts
|

Zero-Dimensional Lead-Free Hybrid Perovskite-like Material with a Quantum-Well Structure

Abstract: Low-dimensional perovskites are an emerging class of materials with high stability and excellent optoelectronic properties. Herein, we introduce a novel, lead-free, zero-dimensional perovskite-like material, (1,3-propanediammonium) 2 Bi 2 I 10 •2H 2 O, for optoelectronic applications. This material exhibited good moisture and thermal stability under ambient conditions. Single-crystal X-ray diffraction analysis revealed a quantum-well structure having the inorganic Bi 2 I 10 4− clusters periodically arranged in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 33 publications
2
62
1
Order By: Relevance
“…As for the lead-based, lead-free perovskites can also be divided to organic–inorganic and all-inorganic. For organic–inorganic lead-free perovskites, standard methylammonium [39,40,50], butylamine [32], 1,3-propanediammonium [51], and phenethylammonium [52] can be used as the A cations. For all-inorganic lead-free perovskites, the most used A cation is Cs, however there are several reports on Rb and Rb/Cs mixture [29,37].…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…As for the lead-based, lead-free perovskites can also be divided to organic–inorganic and all-inorganic. For organic–inorganic lead-free perovskites, standard methylammonium [39,40,50], butylamine [32], 1,3-propanediammonium [51], and phenethylammonium [52] can be used as the A cations. For all-inorganic lead-free perovskites, the most used A cation is Cs, however there are several reports on Rb and Rb/Cs mixture [29,37].…”
Section: Synthesismentioning
confidence: 99%
“…Also due to the presence of a hydrophobic organic chain, it was shown that the (C 6 H 5 NH 3 )BiI 4 perovskite can withstand constant exposure of moisture for one year in ambient. Among the organic–inorganic bismuth-based perovskites, a (1,3-propanediammonium) 2 Bi 2 I 10 ·2H 2 O with quantum-well morphology can be highlighted [51]. This material has sandwich structure with the inorganic Bi 2 I 10 4− clusters periodically arranged in the crystallographic “c” axis separated by 0.5 nm layers of organic cations.…”
Section: Synthesismentioning
confidence: 99%
“…Interestingly, the small band gap of 1.48 eV was comparable to that of (CH 3 NH 3 )PbI 3 , and very close to the ideal band gap . The band gaps of organometal halide perovskites depend on a wide range of factors, including the halogen, the connectivity of the inorganic part, special orbital interaction, and even quantum‐well structure . Compared with 2 , the small band gap of 1 could be owing to the different halogens in the structure.…”
Section: Resultsmentioning
confidence: 99%
“…By introducing organic amines at the A sites in the A a Bi b X a +3 b family, Bi‐based perovskites with different structures have been synthesized (Table ). The optical band gaps can be tuned by changing the halides, according to the sequence Cl>Br>I . Most of the materials have normal 0 D and 1 D inorganic components.…”
Section: Resultsmentioning
confidence: 99%
“…Zero‐dimensional (0D) organic−inorganic hybrid metal halides belong to a class of emerging optoelectronic materials with unique host−guest structures, suggesting large potentials in photodetectors, [ 1 ] white‐light emitting diodes (WLEDs), [ 2 ] X‐ray scintillations, [ 3 ] luminescent sensors, [ 4 ] etc. It is noteworthy that 0D here is defined as the molecular level concept, in which the not‐networked individual metal halide units or clusters act as a judging criteria for this type of materials.…”
Section: Introductionmentioning
confidence: 99%